A promising laccase immobilization approach for Bisphenol A removal from aqueous solutions. (January 2019) - Lassouane, Fatiha; Aït-Amar, Hamid; Amrani, Saïd; Rodriguez-Couto, Susana
Graphical abstract: Highlights: Laccases from T. pubescens were produced by semi solid-state fermentation. Laccase was successfully immobilized by cross-linking plus entrapment. Cross-linking prior to entrapment diminished laccase leakage from the beads. Immobilized laccase removed almost completely 20 mg L −1 BPA in 2 h. BPA (20 mg L −1 ) was efficiently removed in 10 successive batches. Abstract: The immobilization of crude laccase from Trametes pubescens by glutaraldehyde crosslinking prior to entrapment into Ca-alginate beads increased the immobilization yield by 30% and reduced the leaking by 7-fold compared to the immobilization with no crosslinking. The performance of the newly developed biocatalyst to degrade Bisphenol A (BPA) from aqueous solutions was tested. Thus, operating at optimal conditions (i.e. pH 5, 30 °C, 20 mg L −1 BPA and 1500 U L −1 laccase), a BPA removal higher than 99% in 2 h was achieved. This value is higher than those reported to date for BPA removal by immobilized laccases. In addition, the biocatalyst was able to remove BPA in 10 successive batches with an efficiency higher than 70% at the end of the last batch. BPA adsorption on the alginate beads was negligible, therefore BPA removal was only due to laccase action. Moreover, Fourier-transform Infrared (FTIR) spectroscopy suggested BPA transformation by laccase.